The Effect of Community Activities on Water Sources in Kelurahan Pasar Lama - Aziza Rachmania; Devi Arina Mahasina; Mufidah Mufidah; Muhammad Aini Doni Ismadi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Martapura River, a river that is a tributary of the Barito river whose mouth is located in the city of Banjarmasin and upstream is located in Banjar District, South Kalimantan, has experienced pollution that is seen in the physical changes in river water. The city government of Banjarmasin makes the function of the Martapura River a water tourism route so it must be supported by the active participation of the local community. The purpose of this study was to determine the effect of community activities on water resources in the Pasar Lama Kelurahan. The method used in this research is quantitative method. Quantitative methods are used to analyze the data presented in the form of numbers and measured. Next, to determine the status of water quality the Pollution Index method is used. To determine the effect of community behavior in community activities on the banks of the Martapura river and sanitation, descriptive qualitative methods were used through triangulation of data source techniques. The results of the observational analysis showed that the knowledge and attitudes of the community towards PHBS and sanitation activities on average had gone well, but about 25 percent of the people living on the banks of the Martapura River had not implemented their knowledge by tending to do MCK activities and throw garbage directly into the river. Based on observations of the Martapura river that has begun to be polluted, this indicates the existence of pollution from domestic waste disposal in the form of MCK and garbage disposal from traditional market activities. The behavior of the community that still dumps garbage into the river, the existence of traditional markets on the edge of the river, and there are still people who use latrines located in the Martapura river for manci washing latrines which causes the Martapura River is still polluted